Yield Comparison of Three Melon (Cucumis melo L.) Varieties Cultivated with Dutch Bucket and Drip Irrigation Systems - Kumalasari, Widiya Puji; Suwarto, Suwarto; Tini, Etik Wukir; Minarni, Endang Warih (Universitas Padjadjaran, 2024)
Melon is one of the horticultural commodities with considerable economic potential. Cultivation through hydroponic systems can provide efficiency and increase production if complemented by superior varieties. This study aims to identify the best hydroponic system and melon variety combination with the highest yield. The research was conducted from November 2023 to April 2024 at the screen house in Pasir Kulon Village, Karanglewas District, Banyumas Regency, at 110 m above sea level. The study used a split-plot factorial design with a basic design of a Completely Randomized Block Design. The first factor was the hydroponic system, consisting of S1 = Dutch bucket and S2 = drip irrigation. The second factor was the variety, consisting of V1 = Golden Aroma, V2 = Rangipo, and V3 = Sweet Net. The results showed that the best yield was found in the Dutch bucket system and the Golden Aroma variety, with a fruit flesh thickness of 3.3 cm and a total soluble solids content of 17.18 °Brix.